Electroacupuncture versus manual acupuncture for knee osteoarthritis: a randomized controlled pilot trial. Issue 5 (October 2020) - Wang, Tian-Qi; Li, Yong-Ting; Wang, Li-Qiong; Shi, Guang-Xia; Tu, Jian-Feng; Yang, Jing-Wen; Hou, Ya-Quan; Lin, Lu-Lu; Sun, Ning; Zhao, Jing-Jie; Hou, Hai-Kun; Liu, Cun-Zhi
Objective: We aimed to explore the feasibility of evaluating the comparative effectiveness and safety of electroacupuncture (EA) relative to manual acupuncture (MA) for the treatment of knee osteoarthritis (KOA). Methods: A multicenter randomized controlled clinical trial was conducted in Beijing from September 2017 to January 2018. A total of 60 participants with KOA were randomly allocated to either EA ( n = 30) or MA ( n = 30) groups. Participants in the EA group were treated with EA at six to seven local traditional acupuncture points or ah shi points, and two to three distal points. Participants in the MA group had the same schedule as the EA group except that the electrical apparatus featured a working power indicator without actual current output, constituting a sham EA procedure, in order to blind participants. Both groups received 24 sessions over 8 weeks. The primary outcome was response rate, defined as a change of ⩾50% from baseline in the total scores of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) after 8 weeks. Secondary outcomes included pain, stiffness, function, quality of life, and acupuncture-related adverse events (AEs) at 4 and 8 weeks. Results: Of 60 participants randomized, 53 (88%) completed the study. Response rates were 43% for the EA group and 30% for the MA group by the intention-to-treat analysis. Although significant differences were observed in WOMAC pain, stiffness, and function scores within both groups, between-group differences at 8 weeks did not reach statistical significance (odds ratio = 1.75 (95% confidence interval = 0.593–5.162)). Rates of AEs were low and similarly distributed between groups. Conclusion: Both EA and MA interventions in KOA were feasible and appeared safe. Whether or not EA may have a stronger impact on pain and function requires further evaluation through larger, adequately powered, randomized controlled trials. Trial registration number: NCT03274713.